Report on OUM's 2008 Importance-Performance Surveys - Latifah Abdol Latif (2009)
The objective of this paper is to present the findings on OUM’s Importance-Performance Surveys conducted on OUM learners in 2008. The surveys comprised of two components: First on OUM’s undergraduates and second on its post-graduate learners.